Coordination of the closed-loop supply chain for product line design with consideration of remanufactured products. (15th February 2016) - Aydin, R.; Kwong, C.K.; Ji, P.
Abstract: Research on integrated products and the closed-loop supply chain design has focused on the competition and coordination of manufacturers and supply chain partners. However, the coordination of supply chain partners for product line design (PLD) with consideration of remanufactured products has not been addressed in previous studies. The present study investigates the coordination of a manufacturer and supply chain partners using a game theoretical model for the design of product lines that contain both new and remanufactured products. A multiobjective optimization model based on Stackelberg game theory is formulated to determine the product line solutions, pricing decisions of supply chain partners, and product return rate for remanufacturing. A non-dominated sorting genetic algorithm II is introduced to determine the Pareto optimal solutions of the multiobjective optimization problems. A case study is conducted on the coordination of a manufacturer, chain retailers, and a remanufacturer for the PLD of tablet PCs with consideration of remanufactured tablet PCs to illustrate the applicability and effectiveness of the proposed methodology. Highlights: Coordination of a manufacturers and supply chain partners. A multiobjective optimization model based on Stackelberg game theory. Determination of specifications of new and remanufactured products. Pricing of new and remanufactured products. Determination of product return rate for remanufacturing.